THE EFFECT OF LEARNING STYLES, LEARNING INTEREST, LEARNING HABITS, PEERS, AND PARENTAL EDUCATION ON STUDENTS' CRITICAL THINKING SKILLS SMA N 1 KOTO BALINGKA - Afdi, Raski; Jolianis; Mona Amelia (Journal of Practice Learning and Educational Development, 2026)
This study aims to analyze: 1) The influence of learning styles on critical thinking skills, 2) The influence of learning interests on critical thinking skills, 3) The influence of learning habits on critical thinking skills, 4) The influence of learning peers on critical thinking skills, 5) The influence of parental education on critical thinking skills. 6) The combined influence of learning style, learning interest, learning habits, peers, and parental education on students' critical thinking skills. The type of research used in this study is associative research. The research was conducted in July 2025. The population in this study was all 10th grade students in the economics subject at SMAN 1 Koto Balingka. The sample size in this study was 116 people. The sampling technique used was Proportional Random Sampling, and the data analysis techniques used were descriptive analysis and inductive analysis, with the assistance of the Eviews and SPSS version 22.0 programs. The results of the study indicate that 1) There is an influence of learning style on critical thinking ability with a coefficient value of 0.187, a calculated t-value > table t-value (8.673 > 1.659), and a significance value of 0.000 < 0.05, 2) The influence of learning interest on critical thinking ability with a coefficient value of 0.247, where the calculated t-value is greater than the table t-value (9.627 > 1.659) and the significance level is 0.000 > 0.05, 3) The influence of learning habits on critical thinking ability with a coefficient value of 0.699, where the calculated t-value is greater than the table t-value (26.712 > 1.659) and a significance level of 0.000 > 0.05, 4) The influence of peers on critical thinking ability with a coefficient value of 0.062, where the calculated t-value is greater than the table t-value (2.912 > 1.659) and the significance level is 0.004 < 0.05, 5) The influence of parental education on critical thinking ability with a coefficient value of 0.041, where the calculated t-value is greater than the table t-value (2.006 > 1.659) and the significance level is 0.047 < 0.05. 6) Learning style, learning interest, learning habits, peers, and parental education together (simultaneously) have a significant effect on critical thinking ability. Where the calculated F value is 477.792 > F table 3.93 and the significance value is 0.000 < α = 0.05.